Household Income As A Determinant of Child Labor and School Enrollment in Brazil : Evidence From A Social Security Reform - de Carvalho Filho, Irineu (IMF Working Papers; Working Paper, 2008)
This paper studies the effects of household income on labor participation and school enrollment of children aged 10 to 14 in Brazil using a social security reform as a source of exogenous variation in household income. Estimates imply that the gap between actual and full school enrollment was reduced by 20 percent for girls living in the same household as an elderly benefiting from the reform. Girls' labor participation rates reduced with increased benefit income, but only when benefits were received by a female elderly. Effects on boys' enrollment rates and labor participation were in general smaller and statistically insignificant.